The Effect of Ijarah Lease Income on Net Income at The Indonesian Sharia Bank (Case Study of The Indonesian Sharia Bank in Pinang 2018–2020) - Maulana Malik Hafiz; Tuti Anggraini (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2023)
The background of this research is the effect of ijarah lease income on net income in Indonesian Islamic banks. Net profit will increase when the financing distributed to customers is able to generate high profits, the higher the financing distributed, the higher the income received by the bank. With an increase in the level of financing, it will ultimately increase net profit (net income). With a large net profit, the bank will be able to face competition as well as expand the market, the continuity of the bank's business will be more guaranteed, and the level of financing obtained for each product will be evenly distributed without too much comparison. will make the bank's position more stable and optimize profit gain, even though there is one product that is problematic and poses a risk, but that risk certainly does not significantly affect the bank's business in generating profits because it is still anticipated by financing other products.